Optimization of the ultrafiltration-assisted extraction of Chinese yam polysaccharide using response surface methodology and its biological activity - Xue, Heng-Yue; Li, Jing-Ru; Liu, Yan-Geng; Gao, Qi; Wang, Xiao-Wen; Zhang, Jun-Wei; Tanokura, Masaru; Xue, You-Lin (International Journal of Biological Macromolecules, 2019)
Ultrafiltration is a separation process for purifying and concentrating macromolecular solutions. Using Baiyu yam (Dioscorea opposita Thunb) as the raw material, single-factor experiments, Box–Behnken design (BBD) and response surface methodology (RSM) were employed to investigate the effects of the ultrafiltration pH, temperature and pressure on the extraction rate of Chinese yam polysaccharide (CYP). The constructed regression model is highly significant, and the optimal ultrafiltration-assisted extraction conditions were determined to be the following: pH 6.5, 20 °C and 0.03 MPa. Under these optimal conditions, a CYP extraction rate of 88.7% was achieved. After purification with anion exchange (DE-52) and size-exclusion (Sephadex G-100) columns, the monosaccharide composition of CYP was determined to be 50.8% glucose, 24.2% mannose and 11.8% galactose. Fourier transform infrared (FT-IR) spectroscopy characterization of CYP confirmed the characteristic absorption peaks of the polysaccharides. The microstructure of CYP exhibited characteristics typical of amorphous powders. CYP also exhibited antioxidant activities, including the scavenging of DPPH radicals, hydroxyl radicals and superoxide anion radicals. Moreover, CYP exhibited a relatively strong inhibitory effect on BGC-823 cell growth.